Description of the generalized momentum distribution in finite nuclei within t h e independent-particle shell model - Papakonstantinou, P.; Mavrommatis, E.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2020)
A method for calculating the generalized momentum distribution in finite nuclear systems is presented and discussed within the context of the independent particle shell model. Application to the light closed-shell nuclei 16O and 40Ca is included.